2009
DOI: 10.1371/journal.pone.0005411
|View full text |Cite
|
Sign up to set email alerts
|

Use of Self-Selected Postures to Regulate Multi-Joint Stiffness During Unconstrained Tasks

Abstract: BackgroundThe human motor system is highly redundant, having more kinematic degrees of freedom than necessary to complete a given task. Understanding how kinematic redundancies are utilized in different tasks remains a fundamental question in motor control. One possibility is that they can be used to tune the mechanical properties of a limb to the specific requirements of a task. For example, many tasks such as tool usage compromise arm stability along specific directions. These tasks only can be completed if … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
86
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(91 citation statements)
references
References 43 publications
5
86
0
Order By: Relevance
“…Our results demonstrate that arm posture has a dramatic effect on the ability to regulate endpoint stiffness orientation. These findings help to explain the influence of arm posture on the ability to control unstable loads (Milner 2002) and the discovery that subjects self-select postures that match the orientation of maximal arm stiffness to the stability requirements of the task being performed (Trumbower et al 2009). The influence of posture on endpoint stiffness has been documented in numerous experiments, including passive (Mussa-Ivaldi et al 1985) and active (Gomi and Osu 1998;Perreault et al 2001) conditions.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Our results demonstrate that arm posture has a dramatic effect on the ability to regulate endpoint stiffness orientation. These findings help to explain the influence of arm posture on the ability to control unstable loads (Milner 2002) and the discovery that subjects self-select postures that match the orientation of maximal arm stiffness to the stability requirements of the task being performed (Trumbower et al 2009). The influence of posture on endpoint stiffness has been documented in numerous experiments, including passive (Mussa-Ivaldi et al 1985) and active (Gomi and Osu 1998;Perreault et al 2001) conditions.…”
Section: Discussionmentioning
confidence: 91%
“…Although the central nervous system (CNS) is responsible for the regulation of arm mechanics, we do not yet have a complete understanding of the limits on this regulation and the mechanisms by which it occurs. During unconstrained tasks, posture selection plays a critical role in the regulation of limb mechanics (Milner 2002;Mussa-Ivaldi et al 1985;Trumbower et al 2009). When posture is constrained, however, the nervous system can regulate mechanics only by changing muscle activation through feedforward mechanisms such as cocontraction or feedback mechanisms including the many types of stretch-evoked reflexes Gomi and Osu 1998;Krutky et al 2010;Perreault et al 2002).…”
mentioning
confidence: 99%
“…The initial arm postures in our study did not affect forearm muscle length, so the changes in activity were partly attributed to another mechanism. Trumbower et al (2009) investigated the effects of arm posture on endpoint stiffness using a 3D robotic manipulator and found that arm posture influenced task performance and is a fundamental mechanism to regulate arm stiffness. Therefore, it is likely that our changes in body orientation influenced the participants' ability to compensate for load type.…”
Section: Discussionmentioning
confidence: 99%
“…To provide a natural posture for task execution, the arm of our subjects was not positioned in the horizontal plane. One other study investigating arm stiffness outside of the horizontal plane used a posture with the elbow below the shoulder and hand [35]. The shoulder and hand were both positioned in the horizontal plane.…”
Section: Force Magnitudementioning
confidence: 99%